Music, land and liberation theology: exploring mai Charamba’s ‘Africa’ and Fungisai Zvakavapano-Mashavave’s ‘Hamheno Anoramba’ - Rwafa, Urther; Viriri, Advice; Vambe, M. T. (Taylor & Francis (Routledge), 2016)
http://www.tandfonline.com/doi/abs/10.1080/18125980.2013.852740